(3GdCMcGe GdcHQis - (3YHO GdMb Hf YHO GdQMef Hf YHO Gddg GdCROj GdETHjdj, CHh eMeO, GdeYQha H` GHf GdNQGW,J (B581 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg Hbhdg (B" (3HGH eSde Yf jQjOI , bGd (B: (3ZRG QShd Gddg Udi Gddg Ydjg hSde JSY YTQg ZRhI (B" s
(3BNQgG (B:s
(3Yf GdfHi Udi Gddg Ydjg hSde bGd (B: (3Efi dCQLh Cf dG jYLR Gddg CeJi Cf jDNQge fUa jhe bjd dSYO (B: (3hce fUOb jhe ? bGd NeS eGFI SfI Je GdSaQ GdKGfi s
(3GdfSNI HgG MhGTs
(3cJH ai BNQ GdfSNI HNW eZGjQ (B: (3ced LejY GdOjhGfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B92s
Keywords: (3GdMOjK h GdeUWdMs